Characterization and pathogenicity of six Cytospora strains causing stem canker of wild apple in the Tianshan Forest, China. Issue 3 (3rd March 2020) - Liu, Xiaojie; Li, Xiaoshuang; Bozorov, Tohir A.; Ma, Rong; Ma, Jinbiao; Zhang, Yiheng; Yang, Honglan; Li, Li; Zhang, Daoyuan
Abstract: Cytospora species are capable of causing destructive cankers of stems belonging to a wide range of woody plant species. In severe cases, cankers may lead to dieback of twigs and branches. Little is known about the Cytospora species causing canker disease of wild apple ( Malus sieversii ) trees in the Wild Fruit Forest Reserve in Tianshan Forest, Xinjiang Uygur Autonomous Region, China. In this study, six Cytospora isolates belonging to two species were isolated from cankerous lesions of wild apple twigs. Based on multi‐locus phylogenetic analysis using three DNA markers (ITS, tef1‐α and tub2 ) and morphological characterization, these isolates were identified as Cytospora mali and Cytospora parasitica . Temperature trials (15, 20, 25 and 30°C) showed that the optimal growth temperature for six isolates was 25°C. At a variety of temperatures, C. mali isolates tended to grow faster than isolates of C. parasitica, with the C. mali isolate, EGI1 performing better than others with regard to growth rate. Morphological observations showed that these species exhibited a single locule without conceptacles, and the conidia length was 3–5 μm. In vitro inoculation trials of twigs and leaves of M. sieversii seedlings revealed that the C. mali isolates were highly virulent phytopathogenic fungi, whereas the C. parasitica isolates were less virulent. The isolate EGI1 was the most virulent isolate among the six isolates. This paper presents the first report of pathogenic Cytospora spp. of the M. sieversii Tianshan Wild Fruit Forest Reserve of Yili, Xinjiang in China. It will aid in the understanding of how apple tree cankers are induced and provide disease management guidelines for M. sieversii forest conservation.